In-depth immunophenotyping of patients with glioblastoma multiforme: Impact of steroid treatment. (2nd November 2017) - Chitadze, Guranda; Flüh, Charlotte; Quabius, Elgar Susanne; Freitag-Wolf, Sandra; Peters, Christian; Lettau, Marcus; Bhat, Jaydeep; Wesch, Daniela; Oberg, Hans-Heinrich; Luecke, Stefanie; Janssen, Ottmar; Synowitz, Michael; et al.
ABSTRACT: Despite aggressive treatment regimens based on surgery and radiochemotherapy, the prognosis of patients with grade IV glioblastoma multiforme (GBM) remains extremely poor, calling for alternative options such as immunotherapy. Immunological mechanisms including the Natural Killer Group 2 member D (NKG2D) receptor-ligand system play an important role in tumor immune surveillance and targeting the NKG2D system might be beneficial. However, before considering any kind of immunotherapy, a precise characterization of the immune system is important, particularly in GBM patients where conventional therapies with impact on the immune system are frequently co-administered. Here we performed an in-depth immunophenotyping of GBM patients and age-matched healthy controls and analyzed NKG2D ligand expression on primary GBM cells ex vivo . We report that GBM patients have a compromised innate immune system irrespective of steroid (dexamethasone) medication. However, dexamethasone drastically reduced the number of immune cells in the blood of GBM patients. Moreover, higher counts of immune cells influenced by dexamethasone like CD45 + lymphocytes and non-Vδ2 γδ T cells were associated with better overall survival. Higher levels of NKG2D ligands on primary GBM tumor cells were observed in patients who received radiochemotherapy, pointing towards increased immunogenic potential of GBM cells following standard radiochemotherapy. This study sheds light on how steroids and radiochemotherapy affect immune cell parameters of GBM patients, a pre-requisite for the development of new therapeutic strategies targeting the immune system in these patients.